2003
DOI: 10.1097/01.jom.0000085786.50835.71
|View full text |Cite
|
Sign up to set email alerts
|

Food as a Source of Dioxin Exposure in the Residents of Bien Hoa City, Vietnam

Abstract: Recently, elevated dioxin levels, over 5 parts per trillion (ppt) 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), from Agent Orange was reported in 95% of 43 selected residents of Bien Hoa City, a city in southern Vietnam near a former air base used for Agent Orange-spraying missions. Agent Orange herbicide, contaminated with TCDD, was sprayed in Vietnam between 1962 and 1971 primarily for use as a defoliant. Typical blood TCCD levels are 2 ppt in Vietnamese, but levels are as high as 413 ppt in Bien Hoa City. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…Furthermore, food collected from local markets in Bien Hoa City showed high TCDD levels in fat samples from duck (536-550 ppt lipid), chicken (0.95-74 ppt lipid), and fish (3.2-15349 ppt lipid). These authors suggested that Bien Hoa air base was the origin of this TCDD (Schecter et al, 2003). Our current study, carried out at Bien Hoa air base nearly one decade later, showed lower TCDD levels in human breast milk as compared with those in blood samples reported by Schecter et al (2001).…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, food collected from local markets in Bien Hoa City showed high TCDD levels in fat samples from duck (536-550 ppt lipid), chicken (0.95-74 ppt lipid), and fish (3.2-15349 ppt lipid). These authors suggested that Bien Hoa air base was the origin of this TCDD (Schecter et al, 2003). Our current study, carried out at Bien Hoa air base nearly one decade later, showed lower TCDD levels in human breast milk as compared with those in blood samples reported by Schecter et al (2001).…”
Section: Discussionsupporting
confidence: 47%
“…As herbicides are known to have been spilled at those sites where soil and sediment dioxin levels are found to be high, individuals residing close to these sites are highly likely to have been exposed to such levels (Dwernychuk 2005;Dwernychuk et al 2006). Indeed, previous studies detected elevated TCDD levels in food, wildlife, and subjects from a contaminated area (Schecter et al 2001(Schecter et al , 2002(Schecter et al , 2003Dwernychuk et al 2002). Furthermore, studies recently demonstrated that the mean dioxin levels in soil and breast milk in a sprayed area are significantly higher than those in a non-sprayed area (Nhu et al 2009;Saito et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elevated TCDD levels were measured also in the components of the human food chain (i.e. environmental matrices and living organisms that form the food chain where humans are the ultimate consumers; Dwernychuk et al, 2002), food and wildlife (Olie et al, 1989), as well as in people from the most contaminated areas (Schecter et al, 2001(Schecter et al, , 2002(Schecter et al, , 2003Dwernychuk et al, 2002), in accordance with the general population's route of exposure that proceeds almost exclusively through consumption of animal foods, including meat, fish, and dairy products (Startin and Rose, 2003;EPA, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These are important and good news for people living close to these water bodies. However, the problem of PCDD/F contamination remains relevant for those places, such as the A Luoi valley, that formerly hosted several US bases but are now occupied by villages, where civilians live and extensively rework the contaminated soils for agricultural purposes, as testified by a considerable amount of literature (Olie et al, 1989;Schecter et al, 2001Schecter et al, , 2002Schecter et al, , 2003Dwernychuk et al, 2002;Scott-Clark and Levy, 2003;Stellman et al, 2003;Young et al, 2004;Mai et al, 2007). This is likely affecting TCDD levels in food from this region and the eastern watershed that feeds the Mekong River, but not the southeastern coastal locations object of the present study.…”
mentioning
confidence: 99%